STUDY OF ENVIRONMENTAL IMPACT ASSESSMENT OF THE PRESENTED METHODS FOR QUANTIFYING METOPROLOL AND PROPRANOL ACCORDING TO THE WORLD'S LEADING PHARMACOPOEIAS - Zhuravel, S.V.; Zarivna, Nadiya (SWorld-Ger Conference proceedings, 2025)
The paper presents a study of assessing the environmental impact of the presented methods for quantifying metoprolol according to the world's leading Pharmacopoeias using the Eco-scale method. This method is a comprehensive approach to awarding penalty p